2021
DOI: 10.3389/fneur.2021.691328
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Heart Rate Variability During Sleep Predicts Vagus Nerve Stimulation Outcome Better in Patients With Drug-Resistant Epilepsy

Abstract: Objective: Vagus nerve stimulation (VNS) is an adjunctive and well-established treatment for patients with drug-resistant epilepsy (DRE). However, it is still difficult to identify patients who may benefit from VNS surgery. Our study aims to propose a VNS outcome prediction model based on machine learning with multidimensional preoperative heart rate variability (HRV) indices.Methods: The preoperative electrocardiography (ECG) of 59 patients with DRE and of 50 healthy controls were analyzed. Responders were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…Identifying the precise mechanism of action of VNS in epilepsy may help identify responders vs. non-responders and tailor the treatment to those who will be most likely to benefit. Interestingly, a recent study used a statistical model based on preoperative heart rate variability (HRV) to predict which patients would be suitable for VNS [ 34 ]. Vagal efferents innervate the sinoatrial node and the atrioventricular node to control heart rate [ 35 ].…”
Section: Current Clinical Uses Of Vnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying the precise mechanism of action of VNS in epilepsy may help identify responders vs. non-responders and tailor the treatment to those who will be most likely to benefit. Interestingly, a recent study used a statistical model based on preoperative heart rate variability (HRV) to predict which patients would be suitable for VNS [ 34 ]. Vagal efferents innervate the sinoatrial node and the atrioventricular node to control heart rate [ 35 ].…”
Section: Current Clinical Uses Of Vnsmentioning
confidence: 99%
“…HRV is an indirect reflection of the heart’s autonomic function and VNS has been shown to induce acute increases in HRV [ 36 ]. The investigators found that perioperative HRV indices, recorded during sleep, could better predict response to VNS therapy, compared with measurements recorded during the awake state [ 34 ].…”
Section: Current Clinical Uses Of Vnsmentioning
confidence: 99%
“…Despite the need for more clinical evidence of the benefits of pharmacogenomic applications in epilepsy medicine, here we present the early case for potential economic efficiency for patients with drug-resistant epilepsy. There is also scope for extending the comparators to include neuromodulation options for drug-resistant epilepsy not amenable to surgical intervention, such as vagus nerve stimulation (VNS), [28][29][30][31] anterior nucleus of the thalamus deep brain stimulation, and responsive neurostimulation. [32][33][34][35] VNS 36 and responsive neurostimulation therapy 37 have been found to be cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…A study used machine learning to build prediction models for evaluating responsiveness to VNS therapy preoperatively based on HRV indices in wake and sleep states ( Fang et al, 2021 ). 52 HRV indices were evaluated in 30 responders and 29 non-responders before the implantation of a VNS device.…”
Section: Evidence In Humansmentioning
confidence: 99%